Lexical and Semantic Dimensions of PL-SKT Loanwords: Their Values in King Ramkhamhaeng’s Inscription No.1 - Pimpuang, Kowit; Yuttapongtada, Methawee; Sunghor, Noppawan (Forum for Linguistic Studies, 2025)
The objectives of this research were: (1) to examine the word formation of Pali–Sanskrit (PL-SKT) loanwords in King Ramkhamhaeng’s Inscription No.1; (2) to investigate the semantic changes of these loanwords; and (3) to explore their values across different dimensions in King Ramkhamhaeng’s Inscription No.1. The study focused on a population of 89 PL-SKT loanwords identified in King Ramkhamhaeng’s Inscription No.1, which were systematically selected based on the established word-counting criteria. A qualitative method was employed for analysis in the study. The findings revealed that the 89 PL-SKT loanwords were most commonly formed through primary derivative (Kitaka), followed by compound words (Samāsa), prefixation, (Upasagga) and secondary derivative (Taddhita). Regarding meaning and semantic change, 4 types were identified: narrowing (most frequent), widening, transferring of meaning, and retention of original meaning with the latter being the most prevalent overall. As for their values, the PL-SKT loanwords in the inscription reflect 5 major dimensions: art, language, Buddhism, tradition, and politics. Among these, Buddhism was found to be the most prominent, followed by language, history, politics, and tradition. Therefore, it can be concluded that PL-SKT loanwords are highly valuable and beneficial for illustrating a holistic view of the Sukhothai dynasty, both in its historical context and its lasting influence up to the present.